Food habits of endemic opudi fish (Telmatherina prognatha, Kottelat 1991) in Matano Lake, South Sulawesi, Indonesia - Chadijah Andi; Sulistiono; Ridwan Affandi; Gadis Sri Haryani; Ali Mashar (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Chadijah A, Sulistiono, Affandi R, Haryani GS, Mashar A. 2020. Food habits of endemic opudi fish (Telmatherina prognatha, Kottelat 1991) in Matano Lake, South Sulawesi, Indonesia. Biodiversitas 21: 1373-1378. The opudi fish (Telmatherina prognatha) is endemic fish in Matano Lake, South Sulawesi. This study aims to analyze food habits of the opudi fish. This study was conducted from March 2018 to February 2019 in the Matano Lake at six sampling sites in Lawa River, Wotu pali, Salonsa Beach, Utuno, Petea River, and Tanah Merah. The sampling was taken using bag nets with 0.5 inches of mesh size. Food observation was carried out by examining the stomach of the fish. Analysis of the diet includes index stomach content (ISC), occurrent frequency and index of preponderance (IP). The fish was consisted of 687 males and 478 females. Stomach contents of the fish consisted of three kinds of foods such part of insect, debris and plankton. IP for male consisted of part of insect (58%), debris (13%), and plankton (Nitzschia sp. Eunotia sp. 11%). IP for female consisted of part of insect (33%), Navicula sp. and debris (17%), followed by Nitzschia sp. (13%).